Attraction and retention of previously disadvantaged science research professionals : a case study of the CSIR - thashni.maistry@nrf.ac.za (University of Pretoria, 2013)
Dissertation (MSocSci (Industrial Sociology and Labour))--University of Pretoria, 2011.